دلالة الوقف المتعانق في القرآن الكريم - الشمري، أحمد راضي جبر (جامعة بابل - كلية التربية للعلوم الإنسانية, 2017)
The researcher having cessation and the effective this on texts of Quran . This type' of cessation know by explainers . We can recognized it by two points . If the reader stops on one of them , he can't have the other one . This is from side, From the other side the researcher offered the ideas of Quran's keepers in tis postion. The numbers of this very little in holy Quran comparatively with others by count it .
درس الباحث الوقف المتعانق، وأثره في دلالة النص الكريم، وينماز هذا النوع من الوقف من غيره، بأن له محلين، إذا وقف القارئ على أحدهما لم يجز له الوقوف على المحل الآخر، هذا من ناحية، ومن ناحية أخرى عرض الباحث آراء أصحاب القراءات القرآنية في ما يخص هذا الوقف، وقد أحصى ورود هذا الوقف في القرآن الكريم فوجده قليلاً قياساً بأنواع الوقف الأخرى.
Keywords: القرآن الكريم; الوقف المتعانق; القراءات القرآنية